Improving Listening Skills Through The Cake Application: A Creative Approach To Engaging Students - Laila Alda Suhaila; Lidiyatul Izzah (Indo Green Journal, 2026)
The study aims to evaluate the effectiveness of using the Cake application to improve the listening skills class of VII-1 students at SMP Dharma Karya UT Pondok Cabe. This research employs quantitative methods, utilizing a pre-experimental design comprising pre-tests and post-tests. The sample consists of 30 students in a single class. Tests were used as the primary data collection tool, with pre-tests and post-tests serving as the research instruments. The collected data were statistically analyzed using the paired sample t-test method. The study's results indicate that using the Cake application for teaching listening skills effectively improves students' listening abilities in the class. The average pre-test score was 64.27, while the post-test score was 86.00. At a 5% significance level, the t-count result of 16.586 exceeds the t-table value. Therefore, it can be inferred that there is a significant difference in the pre-test and post-test data for listening learning outcomes using the Cake application.